Poetisk verbalbrug og sproglig datering af gammeltestamentlige tekster - Siegismund, Kasper (Dansk Teologisk Tidsskrift, 2018)
This article includes a short introduction to the general issue of linguistic dating of Old Testament texts as well as an appraisal of the alternative, non-chronological view of linguistic variation that has recently been put forward by Young, Rezetko and Ehrensvärd. Two poetical texts that are generally considered arch aic (Exodus 15 and Judges 5), are examined using an approach to the verbal system in Biblical Hebrew poetry inspired by Alviero Niccacci. In this way it is demonstrated that supposedly archaic preterital use of yiqtol can be explained in other ways – which means that this feature is not a conclusive argument for early dating.